2013
DOI: 10.1097/mol.0b013e32835bcdff
|View full text |Cite
|
Sign up to set email alerts
|

Dietary flavonoids and the development of type 2 diabetes and cardiovascular diseases

Abstract: Evidence from cohort studies and randomized trials suggest beneficial effects of food sources of anthocyanidins (berries) and flavan-3-ols (green tea and cocoa) on cardiovascular health. These findings need to be confirmed in long-term randomized trials, and evaluation of pure compounds will be important to establish what specific flavonoids and doses are effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
107
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(109 citation statements)
references
References 43 publications
1
107
0
1
Order By: Relevance
“…Treatment of diabetic animals with sodium selenite significantly inhibited increasing of serum and kidney lipid peroxidation in comparison with the untreated diabetic animals. Previous studies showed that using natural antioxidants supplements such as vitamin E (32), α-lipoic acid (33), flavonoids (34), oleanolic acid (35), selenium (36), vanadium, α-carotene, zinc, vitamin C (37, 38), aminoguanidine (39), lycopene (40) and natural phenolic compounds have protective effects on lipid peroxidation in diabetics and chronic disease (41). Several reports showed that selenium has neuroprotective effect and in cerebral ischemia and improves antioxidant capacity in vitro and in vivo in patients with coronary artery disease (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of diabetic animals with sodium selenite significantly inhibited increasing of serum and kidney lipid peroxidation in comparison with the untreated diabetic animals. Previous studies showed that using natural antioxidants supplements such as vitamin E (32), α-lipoic acid (33), flavonoids (34), oleanolic acid (35), selenium (36), vanadium, α-carotene, zinc, vitamin C (37, 38), aminoguanidine (39), lycopene (40) and natural phenolic compounds have protective effects on lipid peroxidation in diabetics and chronic disease (41). Several reports showed that selenium has neuroprotective effect and in cerebral ischemia and improves antioxidant capacity in vitro and in vivo in patients with coronary artery disease (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…However, the epidemiologic evidence on the reduction in the chronic disease risk is still limited and usually inconsistent [4,5]. The strongest evidence of their health-protective effects is for cardiovascular diseases [6] and type 2 diabetes [7].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] . Among different polyphenols, flavonoids are most important and are produced as plants secondary metabolites 6 .…”
Section: Introductionmentioning
confidence: 99%